Long Term Contraceptive Method (MKJP) At the Tellu Siattinge Health Center - Malka Mappaewa; Mutmainnah; Ita Novianti (Lembaga Penelitian dan Pengabdian Masyarakat Stikes Panrita Husada Bulukumba, 2023)
ABSTRACT Long-term contraceptive methods are contraception that can be used for a long time, more than 2 years or terminate a pregnancy in a couple who no longer want to have children. The types of methods included in this group are stable contraceptive methods, implants and IUD Intra Uterine Devices which are considered effective and efficient. The purpose of this study was to determine the factors associated with long-term contraceptive use. This research method used a cross sectional design , the population in this study were all couples of childbearing age (PUS) who used long-term contraception, the sample size was 37 women of childbearing age, the sampling technique was purposive sampling. Bivariate data analysis used the Chi-Square test with a 95% confidence level (Î±=0.05). The results showed that there were 33 women of childbearing age using implant contraception and 4 using IUDs. The mother's parity variable had no significant effect with a p value > 0.05. Age, education, knowledge variables have a significant effect with a p value <0.05. In conclusion, factors of age, education and knowledge have an effect on long-term contraceptive use.